Factors Relating To Pregnant Mothers Not Taking Antenatal Care Visits During The Covid-19 Pandemic - Sri Wulan; Novita Br Ginting Munthe; Basyariah Lubis (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Covid 19 is a type of virus that is endemic and can be life-threatening, everyone can be exposed to the virus including pregnant women and pregnant women are one of the groups at risk from the virus, therefore there are pregnant women who do not come to check their pregnancy during this pandemic. Pregnancy check-ups are very important to monitor the condition of the mother and fetus. The sample used was pregnant women who visited for ANC at the Obgyn Clinic at Grandmed Lubuk Pakam Hospital. Sampling technique using accidental sampling technique. The data were analyzed using the chi square test (> 0.05). The results obtained indicate that there is a relationship between age factor and ANC visits (0.02), there is a relationship between education factors and ANC visits (0.00), there is no correlation between parity factors and ANC visits (0.75), there is a relationship between knowledge and visits. ANC (0.04), there is a relationship between husband's support and ANC visits (0.01) and there is no relationship between work and ANC visits (0.19). So it can be concluded that there are 4 factors related to pregnant women not having ANC visits and there are 2 factors that are not related. It is recommended for pregnant women to continue to make ANC visits even during a pandemic using health protocols